2018
DOI: 10.1111/tpj.14107
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis phytochrome A nuclear translocation is mediated by a far‐red elongated hypocotyl 1–importin complex

Abstract: Phytochrome A (phyA) is a red and far-red (FR) sensing photoreceptor regulating plant growth and development. Its biologically active FR-absorbing form Pfr translocates into the nucleus and subsequently regulates gene expression. Two transport facilitators, FR elongated hypocotyl 1 (FHY1) and FHY1-like (FHL), are crucial for its cytoplasmic-nuclear translocation. FHY1 interacts preferentially with activated phyA (Pfr) in assays with recombinant phyA and FHY1 and in vivo. Nuclear translocation of the phyA-FHY1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 58 publications
(92 reference statements)
2
20
0
Order By: Relevance
“…From the perspective of P1-host protein interaction, VIP3/SKI8 turns over the 5′-fragment of RISC-cleaved target RNA, whereas TSN1, TSN2, and VSC are involved in mRNA decapping in stress granules and P-bodies (Branscheid et al 2015 ; Deyholos et al 2003 ; Gutierrez-Beltran et al 2015 ; Sorenson et al 2018 ; Xu and Chua 2009 ). Moreover, a MOS4 modifier, 2 IMPORTINs, and BIG5, which are involved in RNA splicing and RNA transportation, respectively, also interact with P1 Tu (Helizon et al 2018 ; Kitakura et al 2017 ; Luo et al 2013 ; Xu et al 2012 ). In addition, EMA1/SAD2 contains an importin-beta domain that negatively regulates miRNA activity (Wang et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of P1-host protein interaction, VIP3/SKI8 turns over the 5′-fragment of RISC-cleaved target RNA, whereas TSN1, TSN2, and VSC are involved in mRNA decapping in stress granules and P-bodies (Branscheid et al 2015 ; Deyholos et al 2003 ; Gutierrez-Beltran et al 2015 ; Sorenson et al 2018 ; Xu and Chua 2009 ). Moreover, a MOS4 modifier, 2 IMPORTINs, and BIG5, which are involved in RNA splicing and RNA transportation, respectively, also interact with P1 Tu (Helizon et al 2018 ; Kitakura et al 2017 ; Luo et al 2013 ; Xu et al 2012 ). In addition, EMA1/SAD2 contains an importin-beta domain that negatively regulates miRNA activity (Wang et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of OPM is previously highlighted by numerous missense mutations affecting this part of the protein [38,39]. The OPM of phytochromes has been reported to play roles in dimerization [40,41,42], nuclear localization [43,44], and signaling via protein-protein interaction with downstream components [14,45]. It has been suggested that the HKRD is a non-functional kinase domain due to the absence of key conserved residues within the histidine kinase domain [46].…”
Section: Domain Structure Of Plant Phytochromesmentioning
confidence: 99%
“…They interact directly with photoactivated phyA in the cytoplasm through their conserved C-terminal domain, and the phyA-FHY1/FHL complex is imported into the nucleus [62]. More recently, it is reported that the NLS of FHY1 is recognized by importin α (IMPα) independently of phyA, and phosphorylation on serine residues close to the NLS prevents FHY1 binding to IMPα [44]. In the nucleus, the photoactivated phytochromes interact with various downstream signaling components [45].…”
Section: Phytochrome-mediated Light Signaling In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of P1-host protein interaction, VIP3/SKI8 turns over the 5'-fragment of RISC-cleaved target RNA, whereas TSN1, TSN2, and VSC are involved in mRNA decapping in stress granules and P-bodies (Branscheid et al, 2015;Deyholos et al, 2003;Gutierrez-Beltran et al, 2015;Sorenson et al, 2018;Xu and Chua, 2009). Moreover, a MOS4 modi er, 2 IMPORTINs, and BIG5, which are involved in RNA splicing and RNA transportation, respectively, also interact with P1 Tu (Helizon et al, 2018;Kitakura et al, 2017;Luo et al, 2013;Xu et al, 2012). In addition, EMA1/SAD2 contains an importin-beta domain that negatively regulates miRNA activity (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%